INPUT-PROCESS-OUTPUT-OUTCOME QUALITY IN MANAGING EDUCATION IN ELEMENTARY SCHOOLS - Sri Suwartini; Sutama Sutama (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper documents an analysis result of various research articles that discuss aspects of educational quality, either the quality of input, process, output, and outcome. The articles that are analyzed are 20 articles from 2014-2022, which were accredited nationally and non-SINTA. It aims to determine the influence and role of the quality aspects of education that take place in an educational institution on the quality management of education in elementary schools. The type of research is a literature review using a systematic scheme that provides an overview of article publications with the number of data searches at 30 articles. After conducting the review process, 20 articles match the criteria. The research results reveal that there were 9 articles accredited SINTA 3, 2 articles SINTA 2, 3 articles SINTA 4, 2 SINTA articles 5, and 4 non-SINTA articles. Of the 20 articles analyzed, 14 articles discussed input aspects, 4 articles discussed process aspects, 1 article discussed input-process aspects, and 1 article discussed input, process, and output aspects. The analysis results indicate that the input aspects of school principals and teachers have a positive influence and a significant role in managing the quality of education in elementary schools. Nevertheless, there is still a lack of the influence and role of the process, output, and outcome aspects in managing the quality of elementary school education.